Catalytic Conversion From Plastic Waste by Silica-Alumina-Ceramic Catalyst to Produce an Alternative Fuel Hydrocarbon Fraction - Juwono, Hendro; Tri Sujadmiko, M. Arif; Fauziah, Laily; Ayyun, Ismi Qurrota (Jurnal ILMU DASAR, 2019)
Liquid fuels from polypropylene plastic waste have been successfully performed by catalytic cracking method. The catalyst used is Al-MCM-41- Ceramics. The catalyst was characterized by XRD, SEM, Pyridine-FTIR, N2-Adsorption-Desorption, and the product of catalytic cracking were investigated by gas chromatography-mass spectroscopy (GC-MS). The catalyst was using three times at sample notify A,B and C. The results showed liquid fuels have the largest percentage of gasoline (C8-C12) are 92.76; 91.92 and 90.58 percent fraction produced. The performance of catalyst showed that reuseability number were decrease, but the charactersitic of liquid fuel produced were also be agreeable to commercial gasoline standard. Keywords: olypropylene waste plastics, liquid fuels, catalytic conversion, Al-MCM-41-Cer catalyst, reuseability number.